Extensive Myelitis as a Manifestation of Neuroborreliosis - Brás, Ana (2016)
Neurological manifestations of Lyme disease are reported in 3% - 12% of patients, with the most common form of presentation being meningoradiculitis. Other symptoms involving the central nervous system, such as myelitis or encephalitis, are rare (< 5 %). We report a case of a 66-year-old male, with a subacute extensive transverse myelitis, secondary to Borrelia burgdorferi infection. The patient underwent antibiotic therapy filed for neuroborreliosis with a good clinical outcome. The rareness in clinical symptoms and imaging presentation, based on a treatable infectious disease, highlights the importance of the inclusion of neuroborreliosis in the differential diagnosis of longitudinally extensive transverse myelitis.